Pharmacological Profile and Mechanisms of Cardiovascular Protective Effects of Statins: An Update - Abdalla Salem Elhwuegi; Mustafa M. Elfakhri (Libyan International Medical University Journal)
This review article highlights recent developments in the clinical pharmacology of statins. A thorough literature search was performed using PubMed Central, Scopus, and Google Scholar, focusing on keywords related to statin kinetics, mechanisms, cardiovascular protection, side effects, and variations in individual responses. Understanding the pharmacokinetics of statins is essential for maximizing their therapeutic effects while reducing side effects and potential drug interactions. Statins have varying degrees of lipophilicity, resulting in different kinetic profiles that affect their bioavailability, elimination, and interactions with other drugs.